Elevated Hyoid Bone Position in Response to Mandibular Advancing Appliance Predicts Effectiveness of the Appliance for Obstructive Sleep Apnea - Eung-Kwon Pae; Ronald M. Harper (Frontiers Media S.A., 2021)
The objective was to determine whether hyoid bone elevation induced by an anterior mandibular positioning appliance (AMP) predicts the effectiveness of the AMP in patients with obstructive sleep apnea (OSA). Fifteen patients (12 males and 3 females) underwent polysomnographic recordings and lateral cephalograms before and after AMP use of at least 6 months. Measurements of sleep variables and upper airway morphology were compared between pre-AMP and with-AMP states. The AMP appliance reduced apnea-hypopnea indices (AHI) ~53% (33.77 ± 3.29 vs. 15.85 ± 3.78, P = 0.0013). Cephalograms of the oropharyngeal airway showed that the hyoid bone moved superiorly toward the inferior mandibular border (Δ H-MP) ~5 mm (23.4 ± 1.44 vs. 18.27 ± 1.86, P = 0.0377), with the AMP inserted in the oral cavity; no airway measurement other than hyoid bone position changed. No significant correlations emerged between AHI improvement (Δ AHI) and amounts of hyoid elevation (Δ H-MP) when all patients were pooled. However, when the samples were subcategorized, the correlation coefficients increased significantly (P < 0.01) in both subgroups. This outcome suggests the presence of two distinct types among the "Good-Responders" to AMP appliance use. Overall use of the AMP appliance is effective; however, the effectiveness of the appliance appears to depend on the mode of hyoid elevations, likely resulting from muscle responsiveness in patients with AMP use. The results suggest that Δ H-MP measurements may be a useful marker to segregate patients with tongue and hyoid muscles responsive to AMP from those not-so-responsive.